Associations of dietary intake with cardiometabolic risk in a multi-ethnic cohort: a longitudinal analysis of the Determinants of Adolescence, now young Adults, Social well-being and Health (DASH) study. Issue 9 (15th February 2019) - Goff, Louise M.; Huang, Peiyuan; Silva, Maria J.; Bordoli, Claire; Enayat, Elli Z.; Molaodi, Oarabile R.; Cassidy, Aidan; Maynard, Maria; Harding, Seeromanie
Abstract: Unfavourable dietary habits, such as skipping breakfast, are common among ethnic minority children and may contribute to inequalities in cardiometabolic disease. We conducted a longitudinal follow-up of a subsample of the UK multi-ethnic Determinants of Adolescent Social well-being and Health cohort, which represents the main UK ethnic groups and is now aged 21–23 years. We aimed to describe longitudinal patterns of dietary intake and investigate their impact on cardiometabolic risk in young adulthood. Participants completed a dietary behaviour questionnaire and a 24 h dietary intake recall; anthropometry, blood pressure, total cholesterol and HDL-cholesterol and HbA1c were measured. The cohort consisted of 107 White British, 102 Black Caribbean, 132 Black African, 98 Indian, 111 Bangladeshi/Pakistani and 115 other/mixed ethnicity. Unhealthful dietary behaviours such as skipping breakfast and low intake of fruits and vegetables were common (56, 57 and 63 %, respectively). Rates of skipping breakfast and low fruit and vegetable consumption were highest among Black African and Black Caribbean participants. BMI and cholesterol levels at 21–23 years were higher among those who regularly skipped breakfast at 11–13 years (BMI 1·41 (95 % CI 0·57, 2·26), P =0·001; cholesterol 0·15 (95 % CI –0·01, 0·31), P =0·063) and at 21–23 years (BMI 1·05 (95 % CI 0·22, 1·89), P =0·014; cholesterol 0·22 (95 % CI 0·06, 0·37), P =0·007). Childhood breakfast skipping is more common in certain ethnic groups and is associated with cardiometabolic risk factors in young adulthood. Our findings highlight the importance of targeting interventions to improve dietary behaviours such as breakfast consumption at specific population groups.